2022
DOI: 10.1021/acsami.2c09271
|View full text |Cite
|
Sign up to set email alerts
|

Anchoring Bimetal Single Atoms and Alloys on N-Doping-Carbon Nanofiber Networks for an Efficient Oxygen Reduction Reaction and Zinc–Air Batteries

Abstract: Electrocatalysts for the oxygen reduction reaction (ORR) play a central role in fuel cells and zinc–air batteries. Bimetal single atoms and nanoparticle hybrids are emerging ORR electrocatalysts, superior to the most exploited unary metal single-atom catalysts (SACs). Here, we report bimetal SAC-based nanofiber networks of Co3Fe7@Co/Fe-SAC for efficient ORR electrocatalysis and zinc–air batteries. A facile and easy-to-scale-up process is developed, and the versatility is validated in three hybrids. Strong elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…An accelerated durability test was performed to determine the stability of the catalyst and it was found that its current decayed by only 13 mV aer 10 000 cycles. 123 Yan Luo et al synthesized atomically distributed Fe and Co sites in nitrogen-doped carbon nanosheets (A-FeCo@NCNs) through a silica-modied strategy using ZIF-8 and ZIF-67. The synthesized SiO 2 @Fe-ZIF-8/67 was pyrolyzed at 800 °C for 2 h to obtain A-FeCo@NCNs.…”
Section: Metal Nanoparticles + Single-atom Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…An accelerated durability test was performed to determine the stability of the catalyst and it was found that its current decayed by only 13 mV aer 10 000 cycles. 123 Yan Luo et al synthesized atomically distributed Fe and Co sites in nitrogen-doped carbon nanosheets (A-FeCo@NCNs) through a silica-modied strategy using ZIF-8 and ZIF-67. The synthesized SiO 2 @Fe-ZIF-8/67 was pyrolyzed at 800 °C for 2 h to obtain A-FeCo@NCNs.…”
Section: Metal Nanoparticles + Single-atom Catalystsmentioning
confidence: 99%
“…An accelerated durability test was performed to determine the stability of the catalyst and it was found that its current decayed by only 13 mV after 10 000 cycles. 123…”
Section: Fundamentals Of the Orrmentioning
confidence: 99%
“…Rechargeable zinc-air batteries (ZABs) are highly preferred for their high specific energy density, security, and low contamination. However, their commercial application is constrained by the inefficiency of oxygen conversion processes at the air electrode. Currently, Pt-based catalysts are widely applied to oxygen reduction reaction (ORR). The atomic layer deposition (ALD) method was used to put the Pt nanoparticle load on CNTs by Gan et al, which obtained a Pt/CNT catalyst with excellent ORR catalytic activity. Meanwhile, Ru or Ir-based catalysts are applied to oxygen evolution reaction (OER). , A highly universal wet-chemical approach was used to prepare RuO 2 nanowires (NWs) by Yang et al, which showed a lower OER overpotential under acidic and alkaline conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that MN x sites are the main active sites for ORR, and the presence of metal nanoparticles (M-NPs) should be avoided for exposing maximally these active sites . Although some reports suggest that M-NPs encapsulated into few graphene layers can synergistically enhance the ORR. Introducing adjacent metal centers, either in the form of MN x or M-NP, can modulate the electronic structure of M–N–C sites and expedite the ORR kinetics. However, most of the reported studies are on the combination of SACs and M-NPs with the same metal types, and there are very rare reports which signify the synergistic coupling between SACs and M-NPs of different metal centers. This might be because of difficulty in achieving such active composite sites.…”
Section: Introductionmentioning
confidence: 99%